Factors of Dental Caries, Tooth Mobility, and Periodontal Pockets on the Occupation of Tooth Loss in the Elderly. (A Study in Karikil Village, Mangkubumi District, Tasikmalaya City) - Sopianah, Yayah; Murdiastuti, Kwartarini; Amalia, Rosa; Taftazani, Rieza Zulfahmi; Lestari, Ayu Rahayu (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Loss of teeth can disrupt daily activities such as chewing disorders, causing emotional problems, and loss of self-confidence. Tooth loss in the elderly is usually caused by dental caries and periodontal disease which are influenced by several other factors. AIM: This study aims to obtain a mathematical equation for predicting tooth loss in the elderly based on dental caries, tooth mobility, and periodontal pockets which have been shown to have an effect. MATERIALS AND METHODS: This research is a survey research with a cross-sectional design. The research subjects were 210 elderly people from Karikil Village, Mangkubumi District, Tasikmalaya City, sampling using the purposive sampling technique affected tooth loss, while the effects were dental caries, tooth mobility, and periodontal pockets. Tooth loss, dental caries, mobility of teeth, and periodontal pockets were measured using the fill-in format from the World Health Organization. Data analysis used the Chi-square correlation test and multiple logistic regression. RESULTS: The results of the Chi-square test analysis showed that the variables of dental caries and tooth mobility had a very significant effect on tooth mobility (p = 0.000 and 0.007). The pocket periodontal variable did not show a significant relationship to tooth mobility (p = 0.947). The results of the multiple logistic regression analysis of dental caries and tooth mobility together contributed 12.2% (R2 = 0.122) to tooth mobility in the elderly. Dental caries gave the greatest contribution to tooth loss, namely, 87.6%. CONCLUSION: Dental caries gives the greatest contribution compared to tooth mobility and periodontal pockets to the occurrence of tooth loss in the elderly. In the elderly, the higher the level of dental caries and tooth mobility, the higher the risk of tooth loss.